Tabuleiro de evolução biológica: um jogo didático como ferramenta lúdica para o ensino médio - Prado, Beatriz Calaça do (2020)
Evolution is considered a central theme of biology, establishing relationships between existing living beings and the degree of kinship between these species. There are many factorsthat hinder the process of assimilating this content, starting with religious influences, beliefs and cultures, the gap in the training of teachers, the incomplete textbook, the school curriculum. Playful tools can assist this process, motivating students, making the individual able to interpret and give meaning to a certain phenomenon. Thus, it sought to present a didactic game as a recreational tool for teaching Biological Evolution to high school students. A board game was elaborated containing a course to be followed. In it there are three types of boxes for players to move forward or backward in the game by rolling the dice and correctly answering the proposed questions. In the letters, there are questions about the theories of Biological Evolution and statements to answer ‘T’ or ‘F’. The game was applied to three classes of 3rd year of high school at the Unidade Integrada Sesi Senai in Catalão – GO. Participating observation and the writing of a logbook were used throughout the process. The students acknowledged to be more attentive to the theoretical explanations in order to have a better performance in the game, facilitating the route and knowing more content to answer the questions. The results obtained point to ludic activity as a facilitator of learning process.